ENT MCQs for medical students : with explanatory answers - Mannu, Gurdeep Singh; Odutoye, Tunde; Soma, Sameer (London : CRC Press, Taylor & Francis Group, 2010)
Ear, Nose and Throat (ENT) surgery has traditionally been a difficult and specialised topic in undergraduate medicine and for junior doctors. Many textbooks are too detailed for undergraduate use, or lack self assessment questions to help those wishing to underpin their learning. This concise and easy-to-read self-assessment guide aims to clarify the topic, and find and fill gaps in understanding. The multiple choice questions (MCQs) contained cover all levels of knowledge and the learning objectives of most of the UK medical school curricula, aiding preparation for end of unit, module and final exams for ENT. This book will be a valuable companion for clinics and teaching sessions and an indispensable revision primer for graduate entry medical curricula. 'An excellent means of preparation for medical undergraduate examinations as gaps in core knowledge are quickly revealed. Further, this text is a good guide for students to identify those subject areas requiring more focused study, especially when time is short.' - From the Foreword by Samir Soma
The Ear -- The Nose -- The Throat -- Head -- Neck -- Surgery.
Includes index.
Includes bibliographical references.
Keywords: Otolaryngology -- Examinations, questions, etc; Otolaryngology -- Study guides